In vitro germination of lemon cui (Citrus microcarpa Bunge) - Pagalla, Devi Bunga; Kandowangko, Novri Youla; Ahmad, Jusna; Febriyanti, Febriyanti (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
Lemon cui (Citrus microcarpa Bunge) is widely utilized by the people of Gorontalo as a cooking ingredient, traditional medicine, cleaning agent, and cosmetic ingredient. This diversity of uses indicates the potential for further development of lemon cui. The initial stage of development that can be undertaken is the mass propagation of high-quality lemon cui seedlings. This study aims to produce lemon cui seedlings using in vitro culture techniques through seed germination.The experimental design used in this study is a Completely Randomized Design (CRD) with four treatments, namely:  A: MS0 (without the addition of plant growth regulators and young coconut water); B: MS + 50 mL young coconut water + 0.5 ppm 2,4-D; C: MS + 50 mL young coconut water + 1 ppm 2,4-D; and D: MS + 50 mL young coconut water + 1.5 ppm 2,4-D. The culture medium used was Murashige and Skoog (MS) supplemented with young coconut water and 2,4-dichlorophenoxyacetic acid (2,4-D). The study's results showed that using young coconut water and 2,4-D significantly accelerated the germination of lemon cui seeds. The best result was observed in treatment D, where the citrus seeds exhibited a maximum germination rate of 100%. In addition, the combination of young coconut water and 2,4-D is capable of inducing callus formation during the germination process. The combination of 50 mL of young coconut water and 1.5 ppm 2,4-D is the most effective concentration for inducing germination of lemon cui seeds and callus formation.